Analisis Strategi Pemasaran pada PT Astra Internasional TBK - Shintami Oktavia; Hasiandra Simanjuntak; Putri Sandrina Sitompul; Radhika Narwastu; Maya Martiza Sari; Cecilia Miranda Lumbangaol; Dicky M.C Sinulingga (Departement of Mathematics Education, 2024)
This research aims to determine the analysis of marketing strategies at PT Astra Internasional Tbk. In this research we will carry out an analysis of the company so that we can analyze how marketing from Pt Astra Internasional Tbk. The type of research used is quantitative research using secondary data where we take existing marketing data. The result is to create statistics regarding previous marketing analysis at Pt Astra Tbk so that we can make decisions on future sales. With this research, it is hoped that it can provide motivation to employees to increase sales and support the company's existence.